Integrating IMF Communications and Operations. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2005)
Transparency and communication have become central to the IMF's mission. The main thesis is that an important means of further strengthening the IMF's external communication in the period ahead will be better coordination and integration of communication with the IMF's policies and operations, especially in country work and for major policy initiatives and issues. Options for implementing the IMF's existing external communications strategy that can be accommodated within existing budget limits are highlighted for discussion.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet